Indonesian Vocabulary Acquisition by Children of Indonesian-Japanese Mixed Marriages on the Ueno Family Japan YouTube Channel (Phonological Study) - Maha; Hany Uswatun Nisa; Prasetyo Yuli Kurniawan (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the acquisition of Indonesian language in bilingual children from a phonological aspect, which includes the acquisition of vowel sounds, consonant sounds, and the factors that influence it. This study uses a qualitative descriptive method. The subjects of the study are two children from a mixed Indonesian-Japanese marriage, namely Ueno Natsuki and Ueno Ritsuki. The data consists of Indonesian vocabulary obtained from 40 vlog episodes on the Ueno Family Japan YouTube channel during the period from January to December 2024. Data collection was conducted through observation (monitoring) methods and recording techniques. Data analysis used intralingual matching methods. The results show that both subjects have mastered and can articulate vowel and consonant sounds accurately and clearly, both at the beginning, middle, and end of words.The vowel sounds include [a], [i], [u], [o], [כ], [e], [ε], and [ə], and the consonant sounds include [b], [c], [d], [g], [h], [j], [k], [l], [m], [n], [p], [q], [r], [s], [t], [v], [w], and [y]. There are several words that have undergone sound changes due to the replacement, addition, or omission of phonemes, resulting in words being pronounced incorrectly and inaccurately.